Pengaruh Struktur Modal dan Likuiditas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Moderasi - Nadhira Putri, Risa; Mutia Basri, Yesi; Afriana Hanif, Rheny (Economic Reviews Journal, 2025)
Using business size as a moderating variable, this study analyzes the effect of capital structure and liquidity on firm value. The focus of the study is on technology sector companies listed on the Indonesia Stock Exchange between 2021 and 2023. Stock prices reflect investors' views on firm value. Using secondary data from documentation, a quantitative descriptive study was conducted on 25 of 47 technology companies. The researcher applied MRA and multivariate linear regression in the analysis. The findings show that liquidity has a positive effect on firm value, while capital structure has a negative effect. Business size strengthens the relationship between capital structure and firm value in a profitable way. Liquidity has a significant impact on business value regardless of company size. These results highlight the importance of good liquidity and capital structure management to attract investors, especially in volatile markets. This research deepens the understanding of financial strategy in the IT industry by illustrating that larger companies are better able to overcome capital structure challenges, thereby increasing their market value.